ByzRev 05.2023.026: Sverrir Jakobsson, The Varangians. In God’s Holy Fire. 2020 / Michal Téra, Kyjevská Rus. 2019 / Georgios Th. Kardaras (ed.), Το Βυζάντιο και η Ρωσία του Κιέβου. 2020 - Shepard, Jonathan (The Byzantine Review, 2023)
Sverrir Jakobsson, The Varangians. In God’s Holy Fire (New Approaches to Byzantine History and Culture). Cham: Palgrave Macmillan 2020. XVIII + 212 pp. + 10 illustrations. – ISBN 978-3-03-053796-8 Michal Téra, Kyjevská Rus. Dějny, Kultura, Společnost / Kievan Rus. History, Culture, Society (Russia altera 34). Pardubice: Pavel Mervart 2019. 721 pp + illustrations + maps. – ISBN 978-80- 7465-413-8 Georgios Th. Kardaras (ed.), Το Βυζάντιο και η Ρωσία του Κιέβου / Byzantium and Kievan Rus' (882--1240) (Το Βυζάντιο σήμερα 8). Athens: National Hellenic Research Foundation 2020. 270 pp. – ISBN 978-9-60-790560-4